Vývoj poptávky a marketingové aktivity maloobchodníků - Starzyczná, Halina; Sýkorová, Pavla (Vysoké učení technické v Brně, Fakulta podnikatelská, 2012)
Purpose of the Article: In 2010, there was a drop in retail sales in the Czech Republic. In the centre of our attention is a question of how the retailers react to this drop, if they appropriately use the recommended marketing activities that are suggested by the theory, especially the retailers, whose sales declined in the given year. Aims: We have set a descriptive goal of the research, that is the definition and characteristics of how (in respect to marketing activities) the retailers react to changes in consumer demand and what is the absolute and relative frequency of these activities. At the same time we will look for the causes of their behaviour. In this paper we will focus on the retailers with declining revenues. Methodology/methods: The methodological approach was chosen in steps from general to specific (inductive method). The theory was examined at the theoretical level by a debate of the regarded issues with respect to the marketing macro-environment and its economic component and the Trading down strategy in response to the decrease in consumer demand. Also the current trade is described. The empirical part presents a brief characterization of the trade in regards to the whole macro-economic environment of the CR, and it also covers the preliminary results of the descriptive primary research focused on the marketing activities of the retailers in the areas of assortment, pricing, personnel and shopping atmosphere. Three descriptive hypotheses were set, regarding the extent of the use of marketing activities. Findings: Both positive and negative symptoms of the use of marketing activities were found, with regard to the recommended Trading down strategy. Most retailers in the sample are small enterprises, which corresponds to the structure in the CR. Entrepreneurs are on the market for more than 10 years and mostly at the municipal level. Conclusions: Retailers with the decline in sales in the reviewed period have actively applied the realization of recommended pricing activities, as well as personnel policy, although that only to a lesser extent. At the same time they have abandoned a significant amount of planned activities concerning the shopping atmosphere. Most of them were passive to the possibility of changing the assortment to improve the structure of the supply and their own economic situation.
The Development of Demand and Marketing Activities of Retailers
Keywords: marketing environment; economic environment; drop of demand; strategy trading down; marketing activities of retailers